1995
DOI: 10.1007/bf00304515
|View full text |Cite
|
Sign up to set email alerts
|

c-kit-Dependent development of interstitial cells and electrical activity in the murine gastrointestinal tract

Abstract: In vivo injection of a neutralizing, monoclonal antibody (ACK2) to the receptor tyrosine kinase (c-kit) disrupts the normal motility patterns of the mouse small intestine. Immunohistochemical studies showed that cells expressing c-kit-like immunoreactivity (c-kit-LI) decreased in numbers in response to ACK2, but the identity of these cells is unknown. We investigated the identity and development of the cells that express c-kit-LI in the mouse small intestine and colon. Cells in the region of the myenteric plex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

16
212
1

Year Published

1996
1996
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 223 publications
(229 citation statements)
references
References 48 publications
16
212
1
Order By: Relevance
“…ICC in the stomachs of wild-type (+/+) and mutant (WIWv) mice were examined with antibodies to c-Kit, a specific marker for ICC in murine GI muscles (11)(12)(13)(14). Two types of cells expressed c-Kit-like immunoreactivity (c-Kit-LI) in wild-type animals.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…ICC in the stomachs of wild-type (+/+) and mutant (WIWv) mice were examined with antibodies to c-Kit, a specific marker for ICC in murine GI muscles (11)(12)(13)(14). Two types of cells expressed c-Kit-like immunoreactivity (c-Kit-LI) in wild-type animals.…”
Section: Resultsmentioning
confidence: 99%
“…A parallel arrangement could exist in which ICC and smooth muscle cells are jointly innervated, or neurotransmission could be a serial process in which ICC provide the critical link between neurons and muscle cells. Recently, it was shown that mutations in c-kit, a protooncogene located at the W locus on chromosome 5 in the mouse that encodes a receptor tyrosine kinase (10), or in stem cell factor, the natural ligand for c-Kit receptors, result in developmental defects in some classes of ICC (11)(12)(13)(14). For example, ICC in the myenteric plexus region (IC-MY) of the small intestine are greatly decreased in numbers in these mutants and slow waves are abolished, confirming a role for IC-MY as pacemakers (3,15,16).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…7) ICCs express the proto-oncogene c-kit, 8) and signalling via the receptor kinase gene product, Kit, is essential for the development of phenotype and electrical rhythmicity. 9) Although ICCs express c-kit receptors, it is not established whether these are functional in the adult, although they are important in developing cells. Imatinib mesylate (Glivec ® ; Novartis Pharmaceuticals) is a selective inhibitor of c-kit receptor tyrosine kinases, and has U.S.A. Food and Drug Administration approval for the treatment of Philadelphia chromosome-positive chronic myeloid leukaemia (CML) and c-kit positive gastrointestinal stromal tumours (GIST).…”
mentioning
confidence: 99%
“…T he Kit receptor tyrosine kinase has a critical role in the normal development and function of the interstitial cells of Cajal (ICC), as well as in hematopoietic cell populations, gametogenesis, and melanogenesis during embryonic development and in the postnatal organism (1)(2)(3). The finding of Kit receptor-activating mutations in human tumors, including gastrointestinal stromal tumor (GIST), seminomas, and mastocytosis, as well as some acute myelogenous leukemias, suggested a role for Kit in oncogenesis.…”
mentioning
confidence: 99%